Analysis of Management Network Using Ubiquiti for Local Office at PT Rizki Inti Madani - Wirawan, Shafwan Abiyu; Tahir, Arib Nawwar; Sutisna, Sutisna (International Journal of Engineering, Science and Information Technology, 2025)
The rapid development of information and communication technology has increased the need for reliable, secure, and efficient computer networks, especially for companies and organizations, including local offices. In this context, stable connectivity and optimal network management significantly impact the company's smooth operation, especially when facing increasingly growing digital transformation challenges. Companies, including the Ubiquiti device, need technology solutions to ensure smooth operations and efficiency. This study aims to provide practical solutions for companies overcoming local office network management problems. This study seeks to optimize network management in companies using Ubiquiti devices, conduct an in-depth analysis of existing network conditions, and design appropriate solutions. This study uses a descriptive qualitative approach, which aims to understand the phenomena that occur in the field in more depth. This approach was chosen because of its ability to explore the meaning, processes, and dynamics that occur in a particular social context. To ensure the successful implementation of the proposed solution, here are some suggestions that PT. Rizki Inti Madani can consider. Human Resources Training and Development, considering the importance of a deep understanding of devices and centralized network management, it is highly recommended that IT technicians and staff involved in network management be given further training on using Ubiquiti and Cisco devices. This training should also include understanding VLAN configuration, QoS, and efficient network troubleshooting and monitoring techniques. Gradual Transition: to reduce the risk of operational disruption, it is recommended that the implementation be carried out in stages. The devices will first be tested in a laboratory environment to ensure the configuration is running as expected. After successful testing, the devices can be installed gradually throughout the office to minimize downtime and operational disruption.